Pengaruh Kepercayaan Konsumen dan Harga Produk yang Dimediasi E-WOM terhadap Keputusan Pembelian di Platform Shopee - Ninggar Agustina Cindya Putri; Siska Hadiyanti; Andriya Risdwiyanto; Sabilla Saberina (Lembaga Pengembangan Kinerja Dosen, 2024)
This study explores the extent to which consumer trust and product price shape purchase decisions on the Shopee platform, with electronic word-of-mouth (e-WOM) functioning as an intervening factor. Employing a quantitative approach, the research involved a sample of 75 undergraduate students residing in boarding houses across the Special Region of Yogyakarta, all of whom are active Shopee users. Data were obtained through structured questionnaires and processed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) technique through SmartPLS version 4. The findings demonstrate that consumer trust and product price exert a significant and positive influence on purchase decisions, both in direct pathways and through the mediating role of e-WOM. This suggests that online reviews, shared experiences, and user-generated recommendations play a pivotal role in shaping consumers’ perceptions and motivating their final choices. The study emphasizes that trust in sellers, perceived price fairness, and the credibility of digital word-of-mouth collectively strengthen consumers’ confidence before making a purchase. These results offer meaningful implications for e-commerce platforms seeking to optimize customer engagement strategies, while also providing consumers with insights into factors that can guide more deliberate and informed buying decisions.